Recovery of Software Architecture from Code Repositories - Ricardo Jorge de Araújo Ferreira (2022)
Architecture can be the result of multiple intangibly connected parts spread across source code and other development artifacts. This makes it difficult to describe the architecture without resourcing to auxiliary documentation that puts this information together. Most of the times, this documentation is manually created, render it a costly process which overtime starts to be desregarded and the documentation becomes out of date and sometimes obsolete. Automating the recovery of the architecture using artifacts that are already present on the source code could potentially improve the way documentation is updated and used.